Radar Cross Section Estimation for a Complex Shaped Objects Using SPSG and PO Methods - Nambari, Dr Swathi (PREPARE@u® | IEI Conferences, 2021)
Radar plays a crucial role in the present war scenario and defence applications. RCS is an important parameter that defines the target cross sectional area. The higher the RCS value, the greater the target detection capability of the Radar. RCS estimation mainly depends on the size, geometry, orientation of the object towards the Radar, and also the material of which the object is made. Among these, the size, geometry, and orientation of the object are considered to be the most significant features in RCS estimation process. RCS determination is an important task for identifying or classifying the objects as either friend or foe. Accurate estimation of Radar Cross Section (RCS) at high frequencies and reduction of radar perceivability at different frequencies is a challenging task. An efficient algorithm is required that can run on a standard PC which provides RCS predictions within a short time. In this paper, Spherical Polar Scattering Geometry (SPSG) and Physical Optics (PO) based algorithms are proposed to estimate RCS of complex structured objects.